2005
DOI: 10.1289/ehp.7588
|View full text |Cite
|
Sign up to set email alerts
|

Association of Housing Disrepair Indicators with Cockroach and Rodent Infestations in a Cohort of Pregnant Latina Women and Their Children

Abstract: Health burdens associated with poor housing and indoor pest infestations are likely to affect young children in particular, who spend most of their time indoors at home. We completed environmental assessments in 644 homes of pregnant Latina women and their children living in the Salinas Valley, California. High residential densities were common, with 39% of homes housing > 1.5 persons per room. Housing disrepair was also common: 58% of homes had peeling paint, 43% had mold, 25% had water damage, and 11% had ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 29 publications
5
95
2
1
Order By: Relevance
“…However, the relationship between building size and mouse allergen turns out to be a complex association. While our results indicated that living in a multistory building is associated with a decrease in the existence of mouse allergen, Chew et al and Cohn et al suggested that higher levels of mouse allergen were associated with living in multistory buildings, low-rise buildings (G8 floors) 9 and high-rise apartments (≥5 floors), 10 62 In addition, we might hypothesize that other neighborhood-level factors, such as proximity to restaurants or grocery stores, or large-scale urban planning projects, could influence the amount of infestation. Area-level predictors may be an especially interesting characteristic to explore in terms of mouse allergen; such that an issue like housing dilapidation at the neighborhood-level could play an important role in explaining this phenomenon.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, the relationship between building size and mouse allergen turns out to be a complex association. While our results indicated that living in a multistory building is associated with a decrease in the existence of mouse allergen, Chew et al and Cohn et al suggested that higher levels of mouse allergen were associated with living in multistory buildings, low-rise buildings (G8 floors) 9 and high-rise apartments (≥5 floors), 10 62 In addition, we might hypothesize that other neighborhood-level factors, such as proximity to restaurants or grocery stores, or large-scale urban planning projects, could influence the amount of infestation. Area-level predictors may be an especially interesting characteristic to explore in terms of mouse allergen; such that an issue like housing dilapidation at the neighborhood-level could play an important role in explaining this phenomenon.…”
Section: Discussioncontrasting
confidence: 68%
“…5,10,24,51,[53][54][55][56][57] Likewise, recent literature has highlighted the relationship between asthma morbidity and building types such as public housing; 54,58 mixed-use buildings, i.e., property containing both residential and commercial space; [59][60][61] and building size. [9][10][11]62,63 Lastly, indoor allergens and asthma morbidity have also been linked to building conditions; in particular older buildings and building violations in or near the residential building have been associated. 8,10,48,49,51,52 However, little explicit examination by building type and condition has occurred, especially in the USA.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
“…The associations that we observed in this study are generally consistent with results from previous studies. 13,18,19 Using a vacuum to clean has been associated with reduced mouse allergen compared with mopping the floor.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, detached housing was more likely to be associated with rodent infestation in another study of homes of immigrant Latinas in Northern California. 18 The investigators in that study speculated that detached houses may offer many points of entry to rodents on the ground level and therefore it may be easier for mice to enter detached homes than to gain access to multilevel dwellings in California. Another possible explanation for our results is that because of the mild climate, detached houses may be less well sealed than multilevel units in Los Angeles, making it easier for mice to enter.…”
Section: Rodent Allergen In Los Angelesmentioning
confidence: 99%
See 1 more Smart Citation